Association Study of MTHFR C677T Polymorphism and Birth Body Mass With Risk of Autism in Chinese Han Population - Zhang, Jishui; Ma, Xueqian; Su, Yi; Wang, Lifang; Shang, Shaomei; Yue, Weihua (Frontiers in Psychiatry, 2021)
Objective: To explore the association of the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism with birth body mass and risk of autism in Chinese Han population. Methods: Totally 1,505 Chinese Han autism patients were recruited, using the diagnosis and statistical manual of mental disorders, 4th revised version (DSM-IV-R) diagnostic criteria for autism. And 1,308 sex-matched healthy controls were also enrolled for the study. All the participants’ birth body masses were counted according to the medical records. The MTHFR C677T genotypes were detected using the polymerase chain reaction- restrict fragment length polymorphism (PCR-RFLP) method. The association between C677T polymorphism, birth body mass and risk of autism were analyzed using the chi-square tests. Results: The present study found that the MTHFR 677T was significantly associated with risk of autism (P = 0.004, OR = 1.18, 95% CI = 1.02-1.29). The autism children showed more frequently with low birth body mass (<2.5kg) than healthy control subjects (8.6% v.s. 5.3%, P = 0.001, OR = 1.67, 95% CI = 1.24-2.26). The interactive effects between MTHFR 677T and low birth body mass (P = 0.0001, OR = 2.18, 95% CI = 1.44-3.32) were also significantly associated with risk of autism. Conclusions: The MTHFR C677T polymorphism, low birth body mass may be associated with risk of autism in Chinese Han population.